GE_GERICHTE A/74/2007 vom 11. Mai 2009 - GE Cour de justice (2009)
; IMPÔT CANTONAL ET COMMUNAL ; ACTIVITÉ LUCRATIVE INDÉPENDANTE ; REVENU D'UNE ACTIVITÉ LUCRATIVE INDÉPENDANTE ; BIEN-FONDS ; IMMEUBLE(ART. 655 CC) ; VENTE | LIPP-IV.1